Interpreting company reports and accounts - Holmes, Geoffrey Andrew; Sugden, Alan.; Gee, Paul. (Harlow, England ; New York : FT Prentice Hall, 2005)
This book guides the reader through the conventions and complexities of company accounts, explaining how to access the financial and trading position of a company from year to year, how to spot undue risk taking and 'cosmetic accounting' and where to look for clues on the quality of management.
Includes index.
aug 04/06/13
Loans
Keywords: Financial statements; Corporation reports; Corporate accounts